AI-Assisted Self-Learning Versus Conventional Demonstration on the Quality of Martial Arts Technique Execution: A Quasi-Experimental Classroom Study - Sudirman (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study investigates the comparative effectiveness of AI-assisted self-learning and conventional demonstration methods in improving the quality of martial arts technique execution among university students. This quasi-experimental classroom study involved 120 students divided into two groups: an experimental group using AI-assisted learning platforms and a control group receiving conventional instructor-led demonstrations. Data were collected through pre-test and post-test assessments using validated rubrics measuring technique accuracy, movement fluidity, speed, and power execution. Independent t-tests and repeated measures ANOVA were employed for statistical analysis. Results demonstrated that the AI-assisted self-learning group achieved significantly higher improvements in technique execution quality (M = 28.45, SD = 4.12) compared to the conventional demonstration group (M = 23.67, SD = 5.38), t(118) = 4.52, p < 0.001, with a large effect size (d = 0.95). Furthermore, the AI group showed greater consistency in performance maintenance across multiple trials. These findings suggest that AI-assisted learning provides personalized feedback mechanisms and repetitive practice opportunities that facilitate superior skill acquisition in martial arts training. The study concludes that integrating AI technology into martial arts pedagogy can complement traditional instruction methods and enhance student learning outcomes.